Stronger Pharmacological Cortisol Suppression and Anticipatory Cortisol Stress Response in Transient Global Amnesia - Griebe, Martin; Nees, Frauke; Gerber, Benjamin; Ebert, Anne; Flor, Herta; Wolf, Oliver T.; Gass, Achim; Hennerici, Michael G.; Szabo, Kristina (Frontiers in Behavioral Neuroscience, 2015)
Transient global amnesia (TGA) is a disorder characterized by a sudden attack of severe anterograde memory disturbance that is frequently preceded by emotional or physical stress and resolves within 24 hours. By using MRI following the acute episode in TGA patients, small lesions in the hippocampus have been observed. Hence it has been hypothesized that the disorder is caused by a stress-related transient inhibition of memory formation in the hippocampus. To study the factors that may link stress and TGA, we measured the cortisol day-profile, the dexamethasone feedback inhibition and the effect of experimental exposure to stress on cortisol levels (using the socially evaluated cold pressor test and a control procedure) in 20 patients with a recent history of TGA and in 20 healthy controls. We used self-report scales of depression, anxiety and stress and a detailed neuropsychological assessment to characterize our collective. We did not observe differences in mean cortisol levels in the cortisol day-profile between the two groups. After administration of low-dose dexamethasone, TGA patients showed significantly stronger cortisol suppression in the daytime profile compared to the control group (p = 0.027). The mean salivary cortisol level was significantly higher in the TGA group prior to and after the experimental stress exposure (p = 0.008; p = 0.010 respectively), as well as prior to and after the control condition (p = 0.022; p= 0.024 respectively). The TGA group had higher scores of depressive symptomatology (p = 0.021) and anxiety (p = 0.007), but the groups did not differ in the neuropsychological assessment. Our findings of a stronger pharmacological suppression and higher cortisol levels in anticipation of experimental stress in participants with a previous TGA indicate a hypersensitivity of the HPA axis. This suggests that an individual stress sensitivity might play a role in the pathophysiology of TGA.